In Vitro Activities of Voriconazole, Fluconazole, and Itraconazole against 566 Clinical Isolates of Cryptococcus neoformans from the United States and Africa - Pfaller, M. A. (American Society for Microbiology, 1999)
We investigated the in vitro activity of voriconazole compared to those of fluconazole and itraconazole against 566 clinical isolates of Cryptococcus neoformans from Africa (164) and the United States (402). Isolates were obtained from cerebrospinal fluid (362), blood (139), and miscellaneous sites (65). Voriconazole (MIC at which 90% of the isolates are inhibited [MIC(90)], 0.12 to 0.25 μg/ml) was more active than either itraconazole (MIC(90), 0.5 μg/ml) or fluconazole (MIC(90), 8.0 to 16 μg/ml) against both African and U.S. isolates. Isolates inhibited by ≥16 μg of fluconazole per ml were almost all (99%) inhibited by ≤1 μg of voriconazole per ml. These results suggest that voriconazole may be useful in the treatment of cryptococcosis.